Custom's future : international law in a changing world - Bradley, Curtis A. (New York, NY : Cambridge University Press, 2016)
Although customary international law has long been an important source of rights and obligations in international relations, there has been extensive debate in recent years about whether this body of law is equipped to address complex modern problems such as climate change, international terrorism, and global financial instability. In addition, there is growing uncertainty about how, precisely, international and domestic courts should identify rules of customary international law. Custom's Future seeks to address this uncertainty by providing a better understanding of how customary international law has developed over time, the way in which it is applied in practice, and the challenges that it faces going forward. Reflecting an interdisciplinary mix of historical, empirical, economic, philosophical, and doctrinal analysis, and containing chapters by leading international law experts, it will be of use to lawyers, judges, and researchers alike.
Custom's past / Emily Kadens -- Customary international law adjudication as common law adjudication / Curtis A. Bradley -- Customary international law as a dynamic process / Brian D. Lepard -- Custom, jus cogens, and human rights / John Tasioulas -- Customary international law : how do courts do it? / Stephen J. Choi and Mitu Gulati -- Custom's method and process : lessons from humanitarian law / Monica Hakimi -- The growing obsolescence of customary international law / Joel P. Trachtman -- The strange vitality of custom in the international protection of contracts, property and commerce / Chin Leng Lim -- The decline of customary international law as a source of international criminal law / Larissa van den Herik -- Customary international law and public goods / Niels Petersen -- Reinvigorating customary international law / Andrew T. Guzman and Jerome Hsiang -- The evolution of codification : a principal-agent theory of the International Law Commission's influence / Laurence R. Helfer and Timothy Meyer -- Custom and informal international lawmaking / Jan Wouters and Linda Hamid -- Custom's bright future : the continuing importance of customary international law / Omri Sender and Michael Wood.
Includes bibliographical references (pages 371-373) and index.
Keywords: Customary law, International; Sources of international law; Law -- International; Customary law, International; International customary law